Development of a Ti-based alloy: Design and experiment - (:unkn) unknown (SPRINGER, 2009)
We proposed the design methodology for titanium-based alloys based on a combination of literature survey, simulation, and experiment. We have selected and investigated the properties of novel Ti-Fe-Zr alloys specifically designed for densification via powder metallurgy techniques. Samples were produced by die compaction of mixed elemental powders with subsequent densification by sintering at 1,275A degrees C in vacuum. Scanning electron microscopy and optical microscopy were used to examine the sintered microstructures to compliment hardness and tensile testing. The results show that density and mechanical properties increase with the iron and zirconium content. The best property combination was obtained with the addition of 5 wt.% iron and 5 wt.% zirconium when vacuum sintered at 1,275A degrees C for 60 min.
Keywords: TITANIUM; COMPOSITES; POWDER